Application Approach Differentiate For Increase Creativity Student History Learning Class X IKM - Julinda*, Farida; Sumantri, Pulung; Arif, Toni (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Based on results reflections of teachers who have done in class X IKM 8 SMA Negeri 1 Medan was found that study This aim For know application approach differentiate in an effort to improve creativity students' History learning class X IKM SMA Negeri 1 Medan. Background in study This is Because lack of creativity student in lesson history like not enough creative Good in ask nor answer, not enough own flexible and flexible traits, also rare give unique and interesting answer. Study This use approach quantitative with steps Classroom action research. Subject in study This is class X IKM 8 consisting of from 29 students. Deep data collection techniques study This is observation teacher activity, observation activity students, and tests question creativity students learn History. Whereas technique analysis the data that is use formula percentage and average. Based on results research that has been carried out, data obtained that application approach differentiate can increase creativity student History learning. This matter is known through analysis results sheet observation cycle I and cycle II which shows exists difference significant in carry out learning in cycle I achieved teacher activities value 68.75% and activity student reached 62.25% with results test reach score 72 and third mark the no reach threshold indicator success in study This ie value 75. In cycle II value activities teachers experience increase until reached 96% and activity student by 94% with results test creativity students' History learning by 97 and third mark the is mark on provision indicator success i.e. 75, then seen that exposure approach differentiate can increase creativity students' History learning class X IKM 8 SMA Negeri 1 Medan